2021
DOI: 10.2478/prilozi-2021-0003
|View full text |Cite
|
Sign up to set email alerts
|

2-Methoxyestradiol Attenuates the Development and Retards the Progression of Hypoxia-And Alpha-Naphthylthiourea-Induced Pulmonary Hypertension

Abstract: Pulmonary arterial hypertension (PH), a progressive, incurable, and deadly disease, predominantly develops in women. Growing body of evidence suggest that dysregulated estradiol (E2) metabolism influences the development of PH and that some of the biological effects of E2 are mediated by its major non-estrogenic metabolite, 2-metyhoxyestradiol (2ME). The objective of this study was to examine effects of 2ME in chronic hypoxia (CH)-induced PH and alpha-naphthylthiourea (ANTU)-induced acute lung injury and PH. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…There is also anecdotal evidence of progesterone receptor expression in the plexiform lesions of a PAH patient, localised to myofibroblasts and modified ECs (Barberis et al, 1995). Furthermore, progesterone offsets the development of PH in ovariectomised female monocrotaline rats, by inhibiting vascular and cardiac remodelling and improving survival (Tofovic, Zhang, & Petrusevska, 2009). Further studies of role of progesterone in PAH pathobiology are clearly warranted.…”
Section: Other Sex Hormone Targets In Pahmentioning
confidence: 99%
“…There is also anecdotal evidence of progesterone receptor expression in the plexiform lesions of a PAH patient, localised to myofibroblasts and modified ECs (Barberis et al, 1995). Furthermore, progesterone offsets the development of PH in ovariectomised female monocrotaline rats, by inhibiting vascular and cardiac remodelling and improving survival (Tofovic, Zhang, & Petrusevska, 2009). Further studies of role of progesterone in PAH pathobiology are clearly warranted.…”
Section: Other Sex Hormone Targets In Pahmentioning
confidence: 99%
“…Similarly, female adult rats present better adaptation with lower PAP than males ( Rabinovitch et al, 1981 ), that worsens after ovariectomy which may be attenuated through estrogens administration ( Earley and Resta, 2002 ). In addition, very recently it has been shown that 2 ME abolishes hypoxia-induced PH in rats associated with a reduced protein expression of hypoxia-inducible factor 1α protein expression, a pro-proliferative mediator ( Docherty et al, 2019 ), reversion of the downregulation of miR-223 ( Hao et al, 2019 ), inhibition of endothelin gene expression ( Earley and Resta, 2002 ) and reducing hematocrit ( Tofovic et al, 2021 ), all suggesting that in female rodents female sex hormones are protective against PH. However, this model translates poorly to human PAH as it lacks some of the main human characteristics of PAH as plexiform lesions and severe RV failure, and PH is almost reversible if the animal is re-exposed to normal room air ( Stenmark et al, 2006 ).…”
Section: The Sex Paradox In Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…In order to rule out any hormonal-related influence on pulmonary hypertension during the estrous cycle (41), all animal experiments were conducted in male mice (8-10 weeks old, ∼25 g body weight). Animal care and handling was performed according to the NIH guidelines.…”
Section: Hypoxia Exposure and Hemodynamic Measurementsmentioning
confidence: 99%